2017
DOI: 10.17511/ijpr.2017.i01.16
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based Study on Co-morbidities in children with severe acute malnutrition

Abstract: Introduction: Severe acute malnutrition, is characterized by wasting (marasmus), oedema (as a result of kwashiorkor), or both (marasmic kwashiorkor), and occurs mostly in children. Globally, co morbidities such as diarrhoea, acute respiratory tract infections and Malaria, which results from a relatively defective immune status, remain the major causes of death among children with severe acute malnutrition. This study was carried out to find out co-morbidities such as infections and micronutrient deficiencies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These findings are consistent with previous reports. 23 On analysis of outcome of SAM cases in this study, it is found that 54% recovered (wt gain >15% of admission wt) and 30% did not respond (wt gain < 10 gm/kg/day) to treatment. Average weight gain and mean duration of hospital stay were 7.5 gm/kg/day and 10.28 ± 5.84 days.…”
Section: Discussionmentioning
confidence: 61%
“…These findings are consistent with previous reports. 23 On analysis of outcome of SAM cases in this study, it is found that 54% recovered (wt gain >15% of admission wt) and 30% did not respond (wt gain < 10 gm/kg/day) to treatment. Average weight gain and mean duration of hospital stay were 7.5 gm/kg/day and 10.28 ± 5.84 days.…”
Section: Discussionmentioning
confidence: 61%
“…This will make it easier for the children to be treated, which will ultimately lead to improved results. Garg, 2017 13 India Cross sectional study 125 severe acute malnourished If several co-morbidities are identified and treated in a timely manner, it is conceivable that the cycle of undernutrition and disease can be broken, leading to a reduction in mortality and an improvement in outcome. Patients with SAM almost universally have insufficient levels of vitamin D. Therefore, a vitamin D supplement must to be administered to each and every SAM sufferer.…”
Section: Resultsmentioning
confidence: 99%
“…Garg, et al (2017) 13 conducted a study with 125 children. They showed 42% of those with this condition also had diarrhoea, and 27% of those with this condition also had acute respiratory tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…These include pneumonia, acute diarrhea/ gastroenteritis, sepsis and anemia. In recent studies on hospitalized children with SAM, pneumonia occurred in 27.8 to 39%, diarrhea in 26.5 to 61% while anemia was observed in 73.5% to 90% [6][7][8][9][10]. True, all grades of anemia do not lead to immediate threat of life, which complications such as pneumonia or gastroenteritis will pose.…”
Section: Anemia In Children With Severe Acute Malnutritionmentioning
confidence: 99%